Differences in Brand Image of Online Chat Application of Blackberry Messenger, Whatsapp, and Line for Bina Nusantara Universityâs Student - Wicaksono, Kuspuji C. B. (Binus Business Review, 2016)
This article was written to find out whether there were any differences on brand image for each online chat Application such as Blackberry Messenger, Whatsapp, and LINE based on six factors of the brand image which are: benefits, attributes, cultures, values, personality, and user. Data for the research were collected from questionnaires given to respondents who had used each mention online chat application. Then each respondent was asked to give scores based on the six factors of brand image for each online chat Application. Using the ANOVA method for testing the differences between brand images for each online chat application. The result reveales that there are differences in the brand image between BlackBerry Messenger, Whatsapp, and LINE for benefits, cultures, and values. There is no difference in attributes, and personality cannot be tested. The company that creates online chat application are expected to improve their brand image to distinguish one another differently.